Iowa RBA, July 7, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for July 7, 1997. Highlights of the update include sightings of a King Rail, Little Blue Herons, and an American Avocet. Also of note were observations of a Worm-eating Warbler in southeast Iowa and Mississippi Kites from four different locations in the central part of the state. Also included are handwritten notes for the next week's update with sightings of a Sabine's Gull and Blue Grosbeak. Epson - sheet feed/flatbed